Diversity Arbuscular Mychorrizal Fungi from Desmodium spp. PT. Cibaliung Sumberdaya, Banten KEANEKARAGAMAN FUNGI MIKORIZA ARBUSKULA (FMA) PADA RHIZOSFER Desmodium spp. ASAL PT. CIBALIUNG SUMBERDAYA, BANTEN - Sri Muryati; Irdika Mansur; Sri Wilarso Budi (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
Ecosystem damage as a result of mining activity is very harmful to the environment. One of the strategy repairing the condition of post-mining land is to use legume cover crops, one type of legume cover crops is Desmodium spp., that has ability to form a symbiosis with AMF and rhizobium. The aim of this study was to determine the diversity of AMF from the four types of rhizosphere Desmodium spp. from PT. Cibaliung Sumber Daya, Banten with different types of host plants. The sampling technique of soil and roots were done by non propotional method. Soil samples were trapped with some types of host plants. Spores were isolated by wet-seaving and decanting technique, then the density of spores was measured and identified. The results showed an increasing number of spore and diversity of AMF. The number of spore before trapped was 10-89 spores per 20 g soil then increased to 16-114 spores per 20 g soil. While the AMF diversity before trapped found only 9 type of spores, consists of 8 type Glomus and 1 type Acaulospora. After trapped increased to 26 spores type AMF consists of 23 type of Glomus and 3 type of Acaulospoara. The root colonization was in range of 22.2 - 95.5%.Key word: Desmodium spp. , Cibaliung, Cover crops.